Inclusion in Education: Research Approaches and Problems - Jasna M. Maksimović; Jelena D. Stamatović (University of Belgrade, Teacher Education Faculty, 2021)
The paper investigates the problems of inclusive education from the perspective of scientific research and with an intention to point to the most pressing problems of inclusive education in Serbia from the researchers' perspective. The analysis encompassed 135 papers focused on different problems related to the research of the inclusive theory and practice and published in the pedagogical literature in the last 10 years. Two units of analysis have been selected: theoretical and problem approach to studying and researching, as well as the methodological approach to the research of inclusive education. The results indicate that, during the first decade after inclusive education had been introduced in Serbia, the authors were dealing mostly with the problems of critical consideration of the conceptual discourse and practice of inclusive education, and very little with the effects of inclusive education. It has been established that empirical papers take prevalence over theoretical ones, while descriptive and survey methods were applied most commonly. The research was carried out using mostly the onesample technique and instruments and no participatory research was conducted. The pedagogical implications refer to the need for a more objective research of the effects of inclusion, given the ten-year period of implementation, and that the research approaches should include all inclusive education actors through participatory and qualitative research in order to offer the guidelines to the creators of the educational reform and its participants in terms of further improvement of the idea and practice of inclusive education.